Memorandum of understanding between Universiti Teknologi MARA and Institute of Technology PETRONAS Sdn. Bhd. / Fakulti Pengurusan Maklumat - Universiti Teknologi MARA, Fakulti Pengurusan Maklumat (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Institute of Technology PETRONAS will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.